Dynamic morphometric changes in degenerative lumbar spondylolisthesis: A pilot study of upright magnetic resonance imaging. (September 2021) - Charest-Morin, Raphaële; Zhang, Honglin; Shewchuk, Jason R.; Wilson, David R.; Phillips, Amy E.; Bond, Michael; Street, John
Highlights: Degenerative lumbar spondylolisthesis (DLS) is more symptomatic in upright posture. Conventional MRI is underestimating the severity of neural compression in DLS. The open MRI can acquire images in the most symptomatic posture in DLS patients. In DLS, the height of the lateral recess is reduced by 50% in the standing posture. The cross-sectional area of the thecal sac is reduced by 30% in standing posture. Abstract: The objectives of this study were to (a) develop a standing MRI imaging protocol, tolerable to symptomatic patients with degenerative spondylolisthesis (DLS), and (b) to evaluate the morphometric changes observed in DLS patients in both supine and standing postures. Patients with single level, Meyerding grade 1 DLS undergoing surgery at a single institution between November 2015 to May 2017 were consented. Patients were imaged in the supine and standing positions in a 0.5 T vertically open MRI scanner (MROpen, Paramed, Genoa, Italy) with sagittal and axial T2 images. The morphometric parameters measured were: cross-sectional area of the thecal sac (CSA), lateral recess height, disc height, degree of anterolisthesis, disc angle, lumbar lordosis, the presence of facet effusion and restabilization signs. Measures from both postures were compared using paired T -test. Associations of posture with the magnitude of change in the various measurements was determined using Pearson correlation or paired T -test when appropriate. All fourteen patients (mean age 64.4 years) included tolerated standing for the time required for image acquisition. All measurements with the exception of lumbar lordosis and disk height showed a statistically significant difference between the postures (p < 0.05). In the standing position, CSA and lateral recess height were reduced by 28% and 50%, respectively. There was no relationship between the change in CSA of the thecal sac and any measures. Standing images acquired in an upright MRI scanner demonstrated postural changes associated with Meyerding grade 1 DLS and images acquisition was tolerated in all patients.